Polycationic redox-active cyclophanes with integrated electron-rich diboron units - Filbeck, Erik; Widera, Anna; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2021)
Cationic cyclophanes are widely used in a variety of applications in supramolecular chemistry and materials science. In this work the authors systematically study the integration of electron-rich diboron units with BII atoms into polycationic cyclophanes with viologen-like electron-acceptor units. They also report a first hexacationic cage-compound in which three diboron units connect two tris(4-pyridyl)triazine acceptor units. Moreover, di- and tetracationic open-structure compounds, in which one diboron unit connects two bispyridyl groups, were synthesized and the properties compared to those of the corresponding closed structures (cyclophanes). The combination of diboron electron-donor units and bi- or oligopyridyl electron-acceptor units leads to intriguing optical and redox properties.
Gesehen am 27.03.2023